Factors Influencing Companies to Engage in Voluntary Internet Financial Reporting: A Review - Ahmed, Hytham Mansour; Ahmed, Abuzar Mohamed (Gezira Journal of Economic and Social Sciences, 2017)
This paper aimed to survey the accounting literature for the supporting factors of voluntary internet financial reporting by corporations. It is generally and widely believed that the Internet may encourage companies to disclose more information and to develop websites for that purpose. However, these tendencies are limited by many concerns on the part of companies and users of companies’ financial information.     Thus, this study surveys the literature for the studies that may fall under any of the two categories. However, Studies that come under the first category have identified various factors that support voluntary internet financial disclosure. These include timeliness and updatability, cost savings, presentation flexibility and feedback, widening information provision among many others. The other category of those studies identified discouraging factors of internet financial reporting that include boarder problem, information overload, reliability, integrity, confidentiality of disclosed data, lack of regulations, access problems among other hampering factors.